2016
DOI: 10.1002/jmv.24612
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two unique naturally occurring Vpr sequence polymorphisms associated with clinical parameters in HIV‐1 chronic infection

Abstract: HIV-1 viral protein R (Vpr) plays important roles in HIV-1 replication. Despite the identification of a number of HLA class I-associated immune escape mutations; it is yet known whether immune-driven Vpr polymorphisms are associated with disease outcome. Hereby, we comprehensively analyzed Vpr sequence polymorphisms and their association with disease outcome and host HLA genotypes, by using plasma viral RNA isolated from 444 HLA-typed, treatment-naïve, chronically HIV-1 infected individuals. Vpr amino acid res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Because these proteins are expressed earlier in the viral life cycle, their recognition may occur before Nef down-modulates HLA class I molecules on the surface of the infected cells and thus provide a window of opportunity to the immune system to clear the infected cell before the virus is released (81). Another CD8+ T-cell epitope predicted by Predivac-3.0 within a cluster region of Vpr is the HLA-A*02:01-restricted peptide AIIRILQQL (82,83), which is located in a functionally important region involved with perinuclear localization of the protein (84,85). This peptide has been shown to correlate inversely with plasma viral load and positively with CD4 count in a study involving a cohort of HIV-1 infected individuals expressing the HLA-A*02:01 allele (80).…”
Section: Discussionmentioning
confidence: 99%
“…Because these proteins are expressed earlier in the viral life cycle, their recognition may occur before Nef down-modulates HLA class I molecules on the surface of the infected cells and thus provide a window of opportunity to the immune system to clear the infected cell before the virus is released (81). Another CD8+ T-cell epitope predicted by Predivac-3.0 within a cluster region of Vpr is the HLA-A*02:01-restricted peptide AIIRILQQL (82,83), which is located in a functionally important region involved with perinuclear localization of the protein (84,85). This peptide has been shown to correlate inversely with plasma viral load and positively with CD4 count in a study involving a cohort of HIV-1 infected individuals expressing the HLA-A*02:01 allele (80).…”
Section: Discussionmentioning
confidence: 99%
“…51,[64][65][66][67]74,76,78 Cross-sectional studies. 49,52,63,[70][71][72][73]75,77,79,[80][81][82]84 Case studies. [63][64][65][66][67] Studies that reported sample types other than blood.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the 63T has been associated with characteristics of slower disease progression. 75,76 When comparing the Vpr sequences between subtypes (Figure 1), subtype C was the only subtype that presented with the 63T substitution. Considering the fact that subtype C has been associated with slower disease progression and replication fitness, [85][86][87][88] it is plausible to speculate that 63T may have a functional role in this outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations at positions 3, 36, 37, 41, 55, 63, 68, 72, and 77 have been associated with variations in the disease progression or the degree of neurocognitive deficit in patients. The simultaneous presence of A55 and T63 in patient-derived Vpr sequences has been associated with lower plasma viral load and higher CD4 count compared with those that express either single or none of these residues [ 167 ]. The impact on the neurocognitive function of patients has been associated with the presence of G41N and A55 (detrimental effect) or I37 and S41 (beneficial effect) [ 168 ].…”
Section: Amino Acid Residues Contributing To Vpr Functionsmentioning
confidence: 99%